2015
DOI: 10.1002/he.20132
|View full text |Cite
|
Sign up to set email alerts
|

From Matriculation to Engagement on Campus: Delineating the Experiences of Latino/a Students at a Public Historically Black University

Abstract: Drawing from a larger study on Asian Americans and Latino/as at HBCUs, this chapter focuses exclusively on the Latino/a students, sheds light on factors that motivated Latino/a students to attend a historically Black university, and discusses the on‐campus experiences of these students. The chapter provides insight into what HBCUs might do to help increase a sense of belonging among Latino/a students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…A change in the campus climate may also help Latinx students succeed at non‐HSIs. For example, Asian and Latinx students at HBCUs tend to find HBCUs supportive and welcoming, and attribute their success to this positive, student‐centered campus climate (Allen, ; Maramba et al., ; Palmer et al., ). White students at HBCUs also report that the institutions have a welcoming, “family‐oriented” environment that provides a “sense of comfort” (Ricard and Brown, :26).…”
Section: Discussionmentioning
confidence: 99%
“…A change in the campus climate may also help Latinx students succeed at non‐HSIs. For example, Asian and Latinx students at HBCUs tend to find HBCUs supportive and welcoming, and attribute their success to this positive, student‐centered campus climate (Allen, ; Maramba et al., ; Palmer et al., ). White students at HBCUs also report that the institutions have a welcoming, “family‐oriented” environment that provides a “sense of comfort” (Ricard and Brown, :26).…”
Section: Discussionmentioning
confidence: 99%
“…Black students comprise 76% of the student body at HBCUs (Palmer et al, 2015) and have a rich history of being in the fore front of most social and educational endeavors on their campuses. Students at this HBCU reported outdoor recreation is not instilled into the campus or Black American cultures and that this affected their willingness to try outdoor activities.…”
Section: Hbcu and Black American Culturesmentioning
confidence: 99%
“…Specifically, scholars have found that Latinx students at HSIs and PWIs share more similar experiences than differences (Nelson-Laird et al, 2007). Researchers have also explored the experiences of Latinx students enrolled at HBCUs (Palmer et al, 2015; Palmer & Maramba, 2015; Roach, 2004). Although HBCU faculty were often more available and approachable to students, Latinx students also experienced microaggression behaviors (e.g., subtle forms of discrimination) from some faculty and their Black peers (Palmer et al, 2015).…”
Section: Review Of Literaturementioning
confidence: 99%